Attachment-Based Family Therapy for Adolescent Substance Use: A Move to the Level of Systems - Lewis, Andrew J. (Frontiers in Psychiatry, 2020)
This paper provides an account of the theoretical basis of a family based intervention called Behaviour Exchange and Systems Therapy (BEST). The model described here has also been applied to adolescents with substance abuse and other mental health problems such as depression and anxiety disorders in both children and adolescents. Evaluative studies of the model have been published including randomised clinical trials as well as qualitative analyses. The current paper discusses a theory of the family system as a discourse and represents an integration of aspects of attachment, psychoanalytic and systems theories. Key concepts elaborated are the attachment-family system, the family as a single discourse, the use of segregation as a defence in relation to trauma and loss and its manifestation in a family narrative, and the role of the family secure base in affect regulation. The paper also briefly describes specific treatment techniques that that are derived from the theoretical model. Our approach has wide application as a discourse focused treatment for children and adolescents using a family systems approach. Future work requires the comparison of this model to similar attachment based models of intervention for children and families, further development and validation of measures able to be used for whole families in a clinical setting, and further empirical demonstration of treatment efficacy in a variety of clinical settings.